Red copper material and preparation method and application thereof

By using copper material in the ceramic copper clad process, combining Zr, Ca, La elements and specific heat treatment processes, the problem of abnormal growth of copper grains caused by high-temperature sintering is solved, and the high performance and small crystals of ceramic copper clad are achieved Grain size.

CN119410952APending Publication Date: 2025-02-11JINTIAN COPPER GROUP CORP NINGBO
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411569881.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing ceramic copper clad technology causes abnormal growth of copper grains during high-temperature sintering, affecting subsequent etching and electrical performance.

Method used

Copper material is used, and its components include 10~100ppm Zr, Ca, and La elements. Through specific deformation heat treatment processes and optimized cleaning processes, grain orientation and surface quality are regulated, and abnormal growth of high-temperature grains are inhibited.

Benefits of technology

It effectively suppresses the abnormal growth of high-temperature grains of copper materials, improves the small grain size, excellent mechanical properties and high surface quality of ceramic copper clad plates, and is suitable for high-power semiconductor modules and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410952A_ABST
    Figure CN119410952A_ABST
Patent Text Reader

Abstract

The invention relates to a red copper material as well as a preparation method and application thereof. The red copper material comprises the following components in percentage by mass: 10-100ppm of at least one element of Zr, Ca and La, and the balance of Cu and inevitable impurities, the grain size of the red copper material is 10-25 microns, the volume percentage ratio L of small-angle grain boundaries and the volume percentage ratio H of large-angle grain boundaries are controlled to be larger than or equal to 2.0 and smaller than or equal to 2.4, the small-angle grain boundaries are grain boundaries with the adjacent grain orientation difference smaller than 15 degrees, and the large-angle grain boundaries are grain boundaries with the adjacent grain orientation difference larger than 15 degrees. According to the method, through specific annealing and cold machining modes and addition of grain refinement elements, high-temperature abnormal growth of grains is inhibited, and meanwhile the surface quality of the red copper material is optimized. The ceramic copper-clad material prepared by taking the obtained red copper material as a substrate can be applied to the fields of automobile connectors, semiconductor coolers, high-power power semiconductor modules and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal processing, and in particular to a red copper material and a preparation method and application thereof. Background Art

[0002] In order to adapt to the development trend of high power, modularization and miniaturization of electronic components in industries such as new energy vehicles, ceramic copper-clad laminates are gradually replacing traditional ceramic aluminum-clad laminates as the substrate material for IGBT (insulated gate bipolar transistor) modules. This is because the composite copper laminate has the characteristics of high thermal conductivity, high insulation, low expansion of ceramic materials, and high electrical conductivity, high thermal conductivity and excellent welding performance of copper materials, making it very suitable for use as a high-power IGBT substrate.

[0003] The current mainstream ceramic copper coating process is the Direct Bonding Copper (DBC) process. This process uses a eutectic bonding method. By adding oxygen between the copper material and the ceramic material, a Cu-O eutectic liquid is formed at a specific temperature to achieve chemical metallurgical bonding between the copper plate and the ceramic substrate. The DBC process has high thermal stability, high mechanical strength, good electrical properties and heat dissipation performance, and compared with traditional methods, the substrate has a higher degree of integration and a smaller size. In order to form a good bond, the process requires high-temperature sintering (>1000°C). At the same time, in order to reduce the copper and ceramic materials (generally Al 2 O 3 )The thermal stress caused by different thermal expansion coefficients requires a period of heat preservation. Since the sintering temperature is much higher than the recrystallization temperature of the copper material, some of the copper grains will grow abnormally, causing warping and other problems, affecting subsequent etching processing. Therefore, it is particularly important to develop a copper material for ceramic copper-clad strip materials suitable for high-power semiconductor modules that does not grow high-temperature grains.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first object of the present invention is to provide a copper material in view of one of the deficiencies of the current technology, wherein the abnormal growth of high-temperature grains of the copper material is suppressed and the grain size of the prepared ceramic copper-clad laminate is small.

[0006] The second object of the present invention is to provide a method for preparing red copper material, which regulates grain orientation through a specific deformation heat treatment process, improves the abnormal growth of copper grains, and improves the surface quality of the copper material by optimizing the cleaning process.

[0007] The third object of the present invention is to provide an application of a red copper material, which can be used in the fields of automotive relays, semiconductor refrigerators, high-power power semiconductor modules, etc.

[0008] The first object of the present invention is achieved by the following scheme: a red copper material, the composition of the material includes: at least one element of Zr, Ca, and La in an amount of 10 to 100 ppm by mass, and the remainder is Cu and inevitable impurities; the grain size of the red copper material is 10 to 25 μm, and the volume percentage of the small-angle grain boundary L and the volume percentage of the large-angle grain boundary H are controlled at 2.0≤L / H≤2.4, wherein the small-angle grain boundary is a grain boundary with an orientation difference of adjacent grains less than 15°, and the large-angle grain boundary is a grain boundary with an orientation difference of adjacent grains greater than 15°.

[0009] Through the above technical scheme, because the orientation degree of the matrix grain structure is limited to 2.0≤L / H≤2.4, within this range, the abnormal growth of high-temperature (>1000℃) grains is controlled, and at the same time, the addition of the above trace elements has an auxiliary inhibitory effect on the abnormal growth of high-temperature grains, so that the final copper material has good mechanical properties and the obtained ceramic copper-clad material has a small grain size.

[0010] Furthermore, the tensile strength of the copper material is 280-380 MPa, the elongation is 15-35%, and the hardness HV is 90-120. Excellent mechanical properties are also required for ceramic copper-clad materials.

[0011] Furthermore, the surface roughness of the copper material is less than 0.25 μm, and the surface glossiness is 280-340 GU. Excellent surface quality is an essential parameter for high-quality chemical metallurgical bonding of the copper material and the ceramic substrate during the ceramic copper coating process.

[0012] Furthermore, the grain size of the ceramic copper-clad plate strip formed by combining the red copper material with the ceramic substrate is less than 145 μm.

[0013] Furthermore, the red copper material is a copper bar material, a copper plate material or a copper strip material.

[0014] The second object of the present invention is achieved by the following scheme: A method for preparing a copper material comprises the following steps:

[0015] Step 1, smelting: first add the electrolytic copper plate and heat it to the smelting temperature. After it is completely melted, add at least one of the copper-zirconium alloy, copper-calcium alloy and copper-lanthanum alloy and keep it warm for 5 to 15 minutes;

[0016] Step 2, semi-continuous casting: pouring high-temperature molten copper into the crystallizer for semi-continuous casting;

[0017] Step 3, ingot processing: hot rolling → first cold working → expansion annealing → second cold working → step annealing → third cold working → low temperature annealing;

[0018] The unfolding annealing is to spread the alloy material out for annealing, and the step annealing is to anneal the copper material with a gradient temperature increase.

[0019] Furthermore, the smelting and semi-continuous casting process is to pour the molten copper into a crystallizer immediately after the raw materials are melted into molten copper for semi-continuous casting.

[0020] Furthermore, the temperature of the hot rolling process is 700-800° C., and the holding time is 3-6 hours.

[0021] Furthermore, the first cold working is rough rolling, the processing rate is 80~95%, and the roll roughness is 0.7~0.9μm; the temperature of the expansion annealing is 600~700℃, and the belt speed is 30~50m / min.

[0022] Furthermore, the second cold working is medium rolling, the processing rate is 20~60%, and the roll roughness is 0.15~0.45μm; the step annealing is first heated to 250~300℃, kept warm for 2~4h, and then heated to 450~550℃, and kept warm for 4~8h.

[0023] Furthermore, the third cold working is finish rolling, the processing rate is 20~45%, the roll roughness is 0.08~0.25μm; the low temperature annealing temperature is 200~280℃.

[0024] Furthermore, after the step annealing, a first cleaning process is also included, using 800 mesh nylon cloth, 1000 mesh non-woven fabric, and 2000 mesh non-woven fabric for cleaning in sequence; after the low-temperature annealing, a second cleaning process is also included, using 800 mesh nylon cloth, 3000 mesh non-woven fabric, and 5000 mesh non-woven fabric for cleaning in sequence.

[0025] The third purpose of the present invention is to use the obtained red copper material in ceramic copper-clad substrate materials in the fields of automotive relays, semiconductor refrigerators, and high-power power semiconductor modules.

[0026] The beneficial effects of the present invention are as follows: through specific annealing and cold working methods, Zr, Ca, La elements and grain orientation are used to exert a synergistic regulatory effect, and the abnormal high-temperature growth of grains inside the copper material is suppressed. At the same time, the roughness of the rolling roller and the number of cleaning brushes are optimized to improve the surface quality of the copper material. The copper material finally has a tensile strength of 280-380 MPa, an elongation of 15-35%, a hardness of 90-120, a grain size of 0.010-0.025 mm, a surface roughness Ra < 0.25 μm, and a glossiness of 280-340 GU. After lamination at a specific temperature, the average grain size of the copper plate is 150 μm. The ceramic copper-clad material prepared with the copper material as a matrix can be used in automotive connectors, semiconductor refrigerators, high-power power semiconductor modules and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a diagram showing the EBSD analysis test results of the low-angle grain boundaries and high-angle grain boundaries of Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention. Unless the context otherwise clearly indicates the opposite, the singular forms used herein are also intended to include the plural forms. The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention. Unless the context otherwise clearly indicates the opposite, the singular forms used herein are also intended to include the plural forms.

[0029] If a part is described as being "on" another part, it may be directly on the other part or there may be other parts therebetween. When a part is described as being "directly on" another part, there may be no other parts therebetween.

[0030] Although not otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those commonly understood by those skilled in the art. Terms with definitions in dictionaries should be interpreted as having the same meaning as those disclosed in the relevant technical literature and this article, and should not be interpreted in an idealized or overly formal sense.

[0031] According to an example of the present invention, a red copper material comprises: at least one element of Zr, Ca, and La in an amount of 10 to 100 ppm by mass, and the remainder is Cu and unavoidable impurities; the grain size of the material is 10 to 25 μm, and the volume percentage of the small-angle grain boundary L and the volume percentage of the large-angle grain boundary H are controlled at 2.0≤L / H≤2.4, wherein the small-angle grain boundary is a grain boundary with an orientation difference of adjacent grains less than 15°, and the large-angle grain boundary is a grain boundary with an orientation difference of adjacent grains greater than 15°.

[0032] First, the reason for limiting the composition of the copper material will be described.

[0033] In the present invention, at least one element of Zr, Ca, and La is added in a mass percentage of 10 to 100 ppm, wherein the above elements are added in the form of copper-zirconium alloy, copper-calcium alloy, and copper-lanthanum alloy, respectively, and after adding the above alloys and keeping them warm for 5 to 15 minutes, semi-continuous casting is immediately performed to reduce the burning loss of the elements. In the present invention, the addition of Zr, Ca, or La elements can, firstly, refine the grains of the casting structure, which is conducive to the full crushing of the grains during subsequent cold working, and lays the foundation for improving the high temperature resistance; secondly, it can significantly reduce the oxygen content in the copper matrix, and prevent the problem of blistering during the high temperature bonding process; in addition, the addition of the above trace elements has an auxiliary effect on inhibiting the abnormal growth of high temperature grains. However, it is difficult to control the homogenization of the components at the ppm level. When the content of the above elements in the matrix is ​​higher than 100 ppm, it is very easy to aggregate and precipitate at the grain boundaries during the solidification of the ingot, increasing the risk of cracking of the copper matrix along the grain. On the contrary, when the content is lower than 10 ppm, the composition is difficult to control due to melting and burning loss, and finally its influence on the abnormal growth of grains is negligible, and the grain refinement effect cannot be achieved. Preferably, the present invention finally selects to add at least one element of Zr, Ca, and La with a mass percentage of 10-100 ppm.

[0034] The copper content of the raw material electrolytic copper plate used in the present invention is greater than 99.99%.

[0035] Then the influence of the structure in copper material is explained.

[0036] The grain size of the copper material of the present invention is 10-25 μm, and the volume percentage of the small-angle grain boundary L and the volume percentage of the large-angle grain boundary H are controlled at 2.0≤L / H≤2.4, wherein the small-angle grain boundary is a grain boundary with an orientation difference of adjacent grains less than 15°, and the large-angle grain boundary is a grain boundary with an orientation difference of adjacent grains greater than 15°. Current research results show that compared with the small-angle grain boundary, the driving force of the large-angle grain boundary migration under high temperature conditions is more improved, and under the drive of the interface energy, the grains are more likely to grow abnormally, so strictly controlling the volume of the large-angle grain boundary can effectively inhibit the high-temperature grain growth of the copper material. In addition, the grain size of the copper material matrix itself should not be too large, so that the grain size of the ceramic copper-clad material finally applied to the ceramic copper-clad substrate is small.

[0037] Let me explain the properties of copper materials.

[0038] According to an example of the copper material of the present invention, the copper material has a tensile strength of 280-380 MPa, an elongation of 15-35%, and a hardness HV of 90-120.

[0039] According to an example of the copper material of the present invention, the surface roughness of the copper material is less than 0.25 μm, and the surface glossiness is 280-340 GU. The surface quality is high, and the chemical metallurgical bonding of the copper plate and the ceramic substrate is easier at a specific temperature. The average grain size of the ceramic copper clad plate is 150 μm, and the bonding quality is also better.

[0040] The copper material of the present invention can be specifically copper bars, copper plates, and copper strips. The ceramic copper-clad material prepared using the copper material as a matrix can be used in the fields of automotive connectors, semiconductor refrigerators, high-power power semiconductor modules, and the like.

[0041] The preparation method of copper material is given.

[0042] A method for preparing a copper material according to an example of the present invention comprises the following steps:

[0043] Step 1, smelting: first add the electrolytic copper plate and heat it to the smelting temperature. After it is completely melted, add at least one of the copper-zirconium alloy, copper-calcium alloy and copper-lanthanum alloy and keep it warm for 5 to 15 minutes;

[0044] Step 2, semi-continuous casting: pouring high-temperature molten copper into the crystallizer for semi-continuous casting;

[0045] Step three, ingot processing: hot rolling → first cold working → expansion annealing → second cold working → step annealing → third cold working → low temperature annealing.

[0046] In the smelting process, first add the electrolytic copper plate and heat it to the smelting temperature. After it is completely melted, add at least one element of Zr, Ca, and La in a mass percentage of 10-100 ppm, wherein the above elements are added in the form of copper-zirconium alloy, copper-calcium alloy, and copper-lanthanum alloy. After the raw materials are melted into copper liquid, the copper liquid is immediately poured into the crystallizer for semi-continuous casting.

[0047] The temperature of the hot rolling process is 700~800℃, and the holding time is 3~6h. In order to achieve sufficient grain refinement, the present invention adopts a lower hot rolling temperature to reduce the size of the hot rolling structure grains, laying the foundation for the subsequent cold working grain crushing. In addition, this process is also a process of homogenizing one or more elements of Zr, Ca, and La, which can further improve the uniformity of the distribution of Zr, Ca or La elements in the matrix. When the hot rolling temperature is higher than 800℃, the hot rolling grains will grow significantly, and small cracks will form on the surface of the hot rolled billet; on the contrary, when the hot rolling temperature is lower than 700℃, due to the good thermal conductivity of the copper matrix, the final rolling temperature will be significantly reduced, and a larger rolling force has to be used for processing, which is not conducive to the control of the dimensional tolerance of the hot rolled billet, and reduces the processing efficiency. Therefore, the present invention finally selects the heating temperature of the hot rolling process to be 700~800℃ and the holding time to be 3-6h.

[0048] The first cold working is rough rolling, with a processing rate of 80-95% and a roll roughness of 0.7-0.9 μm; the temperature of the expansion annealing is 600-700°C and the belt speed is 30-50 m / min. The expansion annealing is to spread the copper strip flat in an air cushion furnace for annealing in a reducing atmosphere, so that the copper strip is heated evenly and the grains grow evenly.

[0049] The second cold working is medium rolling, the processing rate is 20~60%, and the roller roughness is 0.15~0.45μm; the step annealing is first heated to 250~300℃, kept warm for 2~4h, and then heated to 450~550℃, kept warm for 4~8h, and the alloy material is annealed with a gradient temperature increase. Traditional annealing generally uses recrystallization annealing above 400℃, but because cold working will form processing stress in the copper matrix, the stress is unevenly distributed in the copper plate and strip matrix. At the same temperature, the nucleation rate and driving force of grain growth in different regions are also different, resulting in different grain orientations and sizes. This difference will eventually lead to differences in the grain orientation and size of the finished plate and strip, affecting the high temperature resistance of the copper plate and strip. Therefore, the present invention first uses 250~300℃ heating treatment to eliminate part of the processing stress inside the strip, and then performs recrystallization annealing to make the grains grow uniformly.

[0050] The third cold working is finishing rolling, with a processing rate of 20~45% and a roller roughness of 0.08~0.25μm; the low-temperature annealing temperature is 200~280℃, and the heat preservation is 2~5h. The third cold working adopts asymmetric rolling to achieve the regulation of grain orientation, and the volume percentage of small-angle grain boundaries L and the volume percentage of large-angle grain boundaries H are controlled at 2.0≤L / H≤2.4, where small-angle grain boundaries are grain boundaries with an orientation difference of less than 15° between adjacent grains, and large-angle grain boundaries are grain boundaries with an orientation difference of more than 15° between adjacent grains. Compared with small-angle grain boundaries, the driving force of large-angle grain boundary migration is more increased under high temperature conditions, and under the drive of interface energy, grains are more likely to grow abnormally. Since the deformation of the surface and the center of the copper strip is different during cold working, in order to achieve the regulation of grain orientation, asymmetric processing is selected for this cold working, and the speed ratio is controlled between 1.0 and 1.1. Under this condition, the grain orientation can be changed without scratching the strip surface. The present invention achieves the regulation of high-angle grain boundaries and low-angle grain boundaries through the above-mentioned deformation heat treatment process to suppress the abnormal growth of grains in the copper strip material.

[0051] The temperature of the low temperature annealing of the present invention is 200-280°C, and the holding time is 2-5h. The present invention adopts low temperature annealing to eliminate part of the processing stress of the third cold working, but the temperature of the same step annealing process is slightly different. This is because the processing rate of the last cold working is less than that of the second cold working, and the temperature required to eliminate stress is lower. In addition, when the temperature is higher than 280°C, although the grain size of the copper plate strip does not change much, it will rotate and the grain orientation will change, so a low temperature annealing process should be adopted.

[0052] Thus, the obtained copper material has a tensile strength of 280~380MPa, an elongation of 15~35%, a hardness HV of 90~120, and excellent performance.

[0053] In order to improve the bonding effect of DBC, in addition to controlling the grains inside the copper plate, it is also crucial to improve the surface quality of the copper plate strip. In terms of controlling the surface roughness, the present invention controls the roughness of the roller of the first cold working to be 0.7~0.9μm, the roughness of the roller of the second cold working to be 0.15~0.45μm, and the roughness of the roller of the third cold working to be 0.08~0.25μm, and finally controls the surface roughness of the copper plate strip to be less than 0.25μm. In terms of controlling the surface gloss, after the step annealing, it also includes the first cleaning process, using 800 mesh nylon cloth, 1000 mesh non-woven fabric, 2000 mesh non-woven fabric three groups of cleaning brushes for cleaning in sequence; after low-temperature annealing, it also includes the second cleaning process, using 800 mesh nylon cloth, 3000 mesh non-woven fabric, 5000 mesh non-woven fabric three groups of cleaning brushes for cleaning in sequence. During cleaning, the number of brushes increases from small to large, and the brush diameter increases from coarse to fine, and the fineness of the surface texture, the consistency of color brightness, etc. are greatly improved. The glossiness test results show that the glossiness of the front side of the strip is around 280~330GU, and the glossiness of the back side is in the range of 290~340GU. The maximum and minimum difference between the front and back sides is within 40GU.

[0054] The present invention will be further described in detail below in conjunction with the embodiments of the accompanying drawings. However, the present invention can be implemented in various different ways and is not limited to the embodiments described herein.

[0055] The present invention selects 10 embodiments and 6 comparative examples for illustration, and embodiments 1-10 are prepared according to the following steps.

[0056] Example

[0057] 1) Melting: first add electrolytic copper plate and heat it to the melting temperature of 1200~1280℃, after it is completely melted, add at least one element of Zr, Ca, La with a mass percentage of 10~100ppm, wherein the above elements are added in the form of copper-zirconium alloy, copper-calcium alloy and copper-lanthanum alloy respectively, and after adding the above alloy and keeping it warm for 5~15min, cast it immediately to reduce the burning loss of elements;

[0058] 2) Semi-continuous casting: casting temperature is 1180~1250℃, casting speed is 80~140mm / min, and secondary cooling water spray is used at the outlet;

[0059] 3) Hot rolling: heating temperature is 700~800℃, holding time is 3~6h, rolling the ingot to 11~15mm;

[0060] 4) Milling surface: The upper and lower milling surfaces are 0.3~0.6mm to remove the oxide scale and small cracks on the surface of the hot-rolled billet;

[0061] 5) The first cold working: cold working rough rolling, the processing rate is 80~95%, and the roller roughness is 0.7~0.9μm;

[0062] 6) Expanded annealing, using air cushion furnace annealing, annealing temperature is 600~700℃, belt speed is 30~50m / min, and the atmosphere is reducing atmosphere;

[0063] 7) Second cold working: cold working medium rolling, the processing rate is 20~60%, and the roller roughness is 0.15~0.45μm;

[0064] 8) Step annealing: Use bell furnace for annealing, first heat to 250~300℃, keep warm for 2~4h, then heat to 450~550℃, keep warm for 4~8h, and use reducing atmosphere;

[0065] 9) First cleaning: Use three sets of cleaning brushes, 800 mesh nylon cloth, 1000 mesh non-woven cloth and 2000 mesh non-woven cloth, to clean in sequence;

[0066] 10) The third cold working: cold finishing rolling, the processing rate is 20~45%, and the roller roughness is 0.08~0.25μm;

[0067] 11) Low temperature annealing: bell furnace annealing is adopted, the temperature of low temperature annealing is 200~280℃, and the holding time is 2~5h;

[0068] 12) Second cleaning: Use three sets of cleaning brushes, 800 mesh nylon cloth, 3000 mesh non-woven cloth and 5000 mesh non-woven cloth, to clean in turn.

[0069] The details of the ultra-micro alloying elements and key parameters in the present invention are shown in Table 1, the surface roughness and glossiness test are shown in Table 2, and the details of other test data are shown in Table 3.

[0070] The difference between Comparative Example 1 and Example 1 is that no ultrafine alloying elements are added.

[0071] The difference between Comparative Example 2 and Example 1 is that the hot rolling temperature is 850°C.

[0072] The difference between Comparative Example 3 and Example 1 is that the surface roughness of the first cold-processed roller is 1.2 μm.

[0073] The difference between Comparative Example 4 and Example 1 is that no step annealing is performed, the annealing temperature is 450° C., and the temperature is kept for 12 hours.

[0074] The difference between Comparative Example 5 and Example 1 is that the processing rate of the third cold working is 15%, and the roughness of the roll is 0.30 μm.

[0075] The difference between Comparative Example 6 and Example 1 is that the second cleaning is performed using three sets of cleaning brushes, namely, 800-mesh nylon cloth, 1000-mesh non-woven cloth and 2000-mesh non-woven cloth.

[0076] The tensile strength, elongation, hardness, grain size and grain boundary orientation, surface roughness and glossiness of the above-mentioned embodiments and comparative examples were analyzed and tested.

[0077] Tensile strength and elongation test: According to the requirements of GB / T 228.1~2010 Metallic Materials Tensile Test Part 1: Room Temperature Test Method, the test is carried out on an electronic universal mechanical properties testing machine. The test specimen is dumbbell-shaped, the tensile specimen width is 20mm, and the gauge length is A. 50% .

[0078] Hardness test: The test is carried out according to the requirements of "GB / T 4340.0~2009 Metallic Materials Vickers Hardness Test Part 1: Test Method", and the test sample size is 30mm×30mm.

[0079] Grain size and grain boundary orientation detection: The interception point method in "GB / T 6394~2007 Method for Determination of Average Grain Size of Metals" was used to test the grain size in the photos collected by a 100x metallographic microscope, and the test sample size was 10mm×10mm; and large-angle grain boundary and small-angle grain boundary detection: FEI Verios G4 field emission scanning electron microscope equipped with Oxford Symmetry EBSD probe was used for testing, and the test sample size was 10mm×10mm.

[0080] Surface roughness test: According to the rules and requirements of GB / T 1031~1995 Surface roughness parameters and their values, the test was carried out using a Japanese Mitutoyo SJ-210 stylus roughness tester. The test sample size was 200mm×200mm.

[0081] Glossiness test: German BYKAG-4561 metal three-angle gloss meter is used for testing. The test complies with the requirements of "DIN67530-1982 Reflectometer as an auxiliary means for evaluating the brightness of flat coatings (platings) and plastic surfaces" and "ASTMD523-2014 Specular gloss test method". The test sample size is 100mm×100mm.

[0082] Table 1 Ultrafine alloying elements and some key parameters of Examples 1-10 and Comparative Examples 1-6

[0083]

[0084] Table 2 Some key parameters and glossiness of Examples 1-10 and Comparative Examples 1-6

[0085] .

[0086] Table 3 Performance parameters of the corresponding products of Examples 1-10 and Comparative Examples 1-6

[0087]

[0088] It can be seen from Comparative Example 1 that if ultrafine alloying elements are not added, although the performance and grain size of the copper plate and strip material before DBC processing are not much different from those in the embodiment, some grains grow abnormally after processing, and the average grain size is 0.185 mm, which is much larger than the largest grain size of 0.145 mm in Examples 1-10.

[0089] It can be seen from Comparative Example 2 that since the hot rolling temperature is higher than that in the embodiment, the grain size of the copper strip becomes larger, which eventually leads to abnormally grown grains in the DBC process, with a grain size of 0.215 mm, which is not conducive to subsequent etching processing.

[0090] It can be seen from Comparative Example 3 that since the surface roughness of the first cold-processed roller is 1.2 μm, it is difficult to reduce the roughness subsequently, and the surface roughness of the final copper strip rises to 0.38 μm, which is not conducive to the chemical metallurgical bonding of the final copper strip and the ceramic substrate.

[0091] It can be seen from Comparative Example 4 that annealing was performed at 450°C with a holding time of 12 h. Since annealing was not performed under the condition of eliminating processing stress, the proportion of large-angle grain boundaries was high, the grains of the copper strip grew significantly, and the grains grew abnormally after DBC processing.

[0092] It can be seen from Comparative Example 5 that since the processing rate of the third cold working is 15%, the proportion of large-angle grain boundaries is high, the grains of the copper strip have grown significantly, and the roughness of the rolling roller is 0.30μm, and the surface roughness of the copper strip is as high as 0.35μm.

[0093] It can be seen from Comparative Example 6 that since the mesh number of the cleaning brush in the second cleaning is small, the cleaning effect is not thorough and the glossiness of the copper plate strip is relatively high.

[0094] The present invention can be implemented in various ways and is not limited to the above-mentioned embodiments and / or examples. A person skilled in the art can understand that the present invention can be implemented in other specific ways without changing the technical concept or essential features of the present invention. Therefore, it should be understood that the above-mentioned embodiments and / or examples are exemplary and are not intended to limit the present invention.

Claims

1. A copper material, characterized in that: The composition of the material includes: at least one element of Zr, Ca, and La in a mass percentage of 10-100 ppm, and the balance is Cu and inevitable impurities; the grain size of the material is 10-25 μm, and the volume percentage of the small-angle grain boundary L and the volume percentage of the large-angle grain boundary H are controlled at 2.0≤L / H≤2.4, wherein the small-angle grain boundary is a grain boundary with an orientation difference of adjacent grains less than 15°, and the large-angle grain boundary is a grain boundary with an orientation difference of adjacent grains greater than 15°.

2. A copper material according to claim 1, characterized in that: The copper material has a tensile strength of 280-380 MPa, an elongation of 15-35%, and a hardness HV of 90-120.

3. A copper material according to claim 1, characterized in that: The surface roughness of the copper material is less than 0.25 μm, and the surface glossiness is 280-340 GU.

4. The copper material according to claim 1, characterized in that: The grain size of the ceramic copper-clad plate formed by combining the red copper material and the ceramic substrate is less than 145 μm.

5. The copper material according to any one of claims 1 to 4, characterized in that: The red copper material is a copper bar material, a copper plate material or a copper strip material.

6. The method for preparing the copper material according to any one of claims 1 to 4, characterized in that: The steps include: Step 1, smelting: first add the electrolytic copper plate and heat it to the smelting temperature. After it is completely melted, add at least one of the copper-zirconium alloy, copper-calcium alloy and copper-lanthanum alloy and keep it warm for 5 to 15 minutes; Step 2, semi-continuous casting: pouring high-temperature molten copper into the crystallizer for semi-continuous casting; Step 3, ingot processing: hot rolling → first cold working → expansion annealing → second cold working → step annealing → third cold working → low temperature annealing; The unfolding annealing is to spread the copper material out for annealing, and the step annealing is to anneal the copper material with a gradient temperature increase.

7. The method for preparing the red copper material according to claim 6, characterized in that: The smelting and semi-continuous casting process is to melt the raw materials into molten copper and then immediately pour the molten copper into a crystallizer for semi-continuous casting.

8. The method for preparing the copper material according to claim 6, characterized in that: The temperature of the hot rolling process is 700-800° C., and the holding time is 3-6 hours.

9. The method for preparing the red copper material according to claim 6, characterized in that: The first cold working is rough rolling, with a processing rate of 80~95% and a roll roughness of 0.7~0.9μm; the temperature of the expansion annealing is 600~700℃ and the belt speed is 30~50m / min; Preferably, the second cold working is medium rolling, the working rate is 20-60%, and the roller roughness is 0.15-0.45 μm; the step annealing is first heated to 250-300°C, kept warm for 2-4 hours, and then heated to 450-550°C, and kept warm for 4-8 hours; Preferably, the third cold working is finish rolling, the processing rate is 20-45%, the roller roughness is 0.08-0.25 μm; the low-temperature annealing temperature is 200-280° C., and the heat preservation is 2-5 hours; Preferably, after the step annealing, a first cleaning process is also included, using three groups of cleaning brushes of 800 mesh nylon cloth, 1000 mesh non-woven fabric, and 2000 mesh non-woven fabric for cleaning in sequence; after the low-temperature annealing, a second cleaning process is also included, using three groups of cleaning brushes of 800 mesh nylon cloth, 3000 mesh non-woven fabric, and 5000 mesh non-woven fabric for cleaning in sequence.

10. Application of the red copper material according to any one of claims 1 to 4 in ceramic copper-clad substrate materials in the fields of automotive relays, semiconductor refrigerators, and high-power semiconductor modules.

Citation Information

Cited By

  • High-thermal-stability oxygen-free copper strip for power semiconductor device and preparation method of high-thermal-stability oxygen-free copper strip

    CN120366683A

  • High-thermal-stable oxygen-free copper strip for power semiconductor device and preparation method thereof

    CN120366683B

  • Extra-soft red copper strip and grain refinement production process thereof

    CN121674868A